Integrating Digital SCOR and Quality Management in the Textile Industry - Nugraha, Evan; Sari, Rini Mulyani; Norina, Rida (International Journal of Management Science and Information Technology, 2026)
The growing complexity of textile supply chains has increased the need for digital capabilities that enhance operational coordination, process integration, and quality management. The integration of digital supply chain standards with quality management remains important for improving supply chain outcomes in the textile industry. This study examines the relationship between the SCOR Digital Standard (SCOR DS) and Supply Chain Performance (SCP), with Quality Management (QM) serving as a mediating mechanism. A quantitative explanatory approach was employed using data from 320 personnel involved in supply chain, production, quality, and operational activities in the textile industry. Data were collected through structured Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). SCOR DS has a significant positive effect on QM (β = 0.454, p < 0.001) and SCP (β = 0.142, p = 0.009). QM also has a stronger positive effect on SCP (β = 0.484, p < 0.001). Furthermore, QM significantly mediates the relationship between SCOR DS and SCP (β = 0.220, p = 0.007). Digital supply chain capabilities based on SCOR DS can strengthen supply chain performance, particularly when supported by effective quality management. The findings provide an integrated perspective for aligning digital SCOR practices with quality management to improve textile supply chain performance.
Keywords: SCOR Digital Standard; Digital Supply Chain; Quality Management; Supply Chain Performance; Textile Industry